Lysozyme and bovine serum albumin partitioning in polyethylene glycol-phenylalanine conjugate polymer/salt aqueous two-phase systems - Sara Silvério (2012)
Polyethylene glycol (PEG) with average molecular weight of 8000 was used as a model polymer and modified by introducing an amino acid (phenylalanine) in its hydroxyl terminals. The effect of different percentages of the conjugate polymer in relation to the total polymer on binodal curve of PEG-8000-potassium phosphate buffer (KPB), pH 7.2 aqueous two-phase systems and solute partitioning was explored. The partition of lysozyme (Lyz) and bovine serum albumin (BSA) and also of the conjugated polymer was evaluated in ATPS composed of 17% (w/w) total polymer and 12.5% (w/w) KPB, pH 7.2. Lyz partition profile follows the expected trend decreasing with the increase of modified polymer concentration. However BSA shows a partition profile that is approximately symmetrical to the one observed for the partition of the conjugate polymer, which depends on PEG-phenylalanine concentration in the system. Determination of the relative hydrophobicity of the equilibrium phases and of the protein surface hydrophobicity (So) delivered information that shed some light in the mechanisms controlling the partitioning behavior. Therefore, it becomes clear that the hydrophobic character of the protein taken together with the molecular weight explain the different behavior of these two proteins with the increase of PEG-phenylalanine substitution in the systems.